Cinema/politics/philosophy - Baumbach, Nico (Film and culture., 2019)
Film theory and its emphasis on political and ideological readings of films dominated much of cinema studies in the '70s and '80s. Since then, in response to what some view as the shortcomings of theoretical approaches, a variety of other methods have emerged or reemerged. In many ways, as Nico Baumbach argues, "Anti-Grand Theory" has won the day but its victory is, in part, based on misreadings or simplifications of '70s film theory. In particular, Baumbach views contemporary critical approaches to film as abandoning the crucial and productive ways in which theory understands the relationship between cinema, politics and art. Baumbach does not advocate a return to the orthodoxies of the seventies but rather reads the work of Ranciere, Badiou and Agamben as providing new ways of thinking about the history of film theory and how film creates its own way of thinking about politics. Moreover, at a time when digital technologies are asking us to think of film and the film image in new ways, the work of these thinkers once again asks, "What is Cinema?" but in a more expansive sense that can help us account for transformations in how moving images are produced, distributed, and exhibited in the twenty-first century.